Book Review: Romina Meinig (2019): Zwischen Antiziganismus und Rezilienz. Eine empirische Untersuchung erfolgreicher Sinti und Roma in Deutschland. [Between Antigypsyism and resilience. An empirical study about successful Sinti and Roma in Germany.] - Sebestyén, Krisztina (International Dialogues on Education Journal, 2020)
Book Review